2018
DOI: 10.3389/fenrg.2018.00090
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Assessment of a Chopped Feedstock Logistics Supply Chain for Corn Stover

Abstract: Storing corn stover in wet, anaerobic conditions is an active management approach to reduce the risk of significant aerobic degradation and catastrophic loss due to fire. An estimated 50% of the corn stover available in the U.S. is too wet at the time of harvest to be stored safely in baled formats and is compatible with wet, anaerobic storage through ensiling. A logistics system based on field-chopping and particle size reduction early in the supply chain removes the dependency on field-drying of corn stover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 41 publications
1
34
3
Order By: Relevance
“…However, the water that enters with ensiled materials can reduce the water footprint required at the biorefinery and could have positive sustainability impacts. This relationship is out of the scope of this study but has been described elsewhere (Wendt et al, 2018b).…”
Section: Differences In Pretreatment and Enzymatic Hydrolysis Yields mentioning
confidence: 81%
See 2 more Smart Citations
“…However, the water that enters with ensiled materials can reduce the water footprint required at the biorefinery and could have positive sustainability impacts. This relationship is out of the scope of this study but has been described elsewhere (Wendt et al, 2018b).…”
Section: Differences In Pretreatment and Enzymatic Hydrolysis Yields mentioning
confidence: 81%
“…The potential benefits of ensiling in the context of a biorefinery supply system include reduced dependence on seasonality for biomass harvesting thus allowing for a wider harvest window; reduced DML; and reduced fire risk. Ensiling may provide additional benefits by reducing handling and preprocessing challenges, such as size reduction prior to ensiling, negating the need for additional preprocessing at the biorefinery (Wendt et al, 2018b). Reduction in pretreatment severity required for bioconversion of ensiled biomass has been reported by some groups (Essien et al, 2018), but the overall results in the bioconversion between field and lab studies have been variable (Wendt et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sugar production cost was highly sensitive to changes in fungal pretreatment time, glucose yield, and bulk density ( Figure 6 [87][88][89][90][91][92][93][94][95][96][97][98][99]). Variations in the fungal pretreatment time between 7 and 60 days, which are the minimum and maximum values reported in the fungal pretreatment literature used as a data source (Section 2.1.1), produced the greatest change on the sugar production cost for perennial grasses, corn stover, and agricultural residues ( Figure 6).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The primary drawback of wet systems for corn stover is that the moisture in the biomass as well as the bulk, chopped format makes handling this biomass more costly than handling dry, baled biomass. For example, prior research has shown that transportation costs double for chopped corn stover compared to baled stover as a result of reduced bulk density compared to baled biomass (Wendt et al, 2018b). However, the size reduction that can be accomplished during forage chopping that is used in wet logistics systems can reduce both harvest and collection costs as well as the cost of further size reduction during preprocessing.…”
Section: Wet Storage Systemsmentioning
confidence: 99%